1998
DOI: 10.1016/s0886-3350(98)80126-0
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact holmium:YAG laser thermal keratoplasty for hyperopia

Abstract: In this study, Ho:YAG LTK was safe and effective, provided satisfactory correction of low hyperopia, and had a low complication rate. Good patient selection is the key to obtaining good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Hyperopia can be treated with several surgical procedures such as photorefractive keratectomy, 1,2 laser in situ keratomileusis (LASIK), [3][4][5] noncontact laser thermal keratoplasty (LTK), [6][7][8] contact LTK, 9,10 diode laser keratoplasty, 11 thermokeratoplasty, 12 and conductive keratoplasty (CK). [13][14][15][16] Unlike other modalities, CK uses a controlled release of radio-frequency energy that results in localized shrinkage of the stromal collagen directly related to the temperature and duration of exposure.…”
mentioning
confidence: 99%
“…Hyperopia can be treated with several surgical procedures such as photorefractive keratectomy, 1,2 laser in situ keratomileusis (LASIK), [3][4][5] noncontact laser thermal keratoplasty (LTK), [6][7][8] contact LTK, 9,10 diode laser keratoplasty, 11 thermokeratoplasty, 12 and conductive keratoplasty (CK). [13][14][15][16] Unlike other modalities, CK uses a controlled release of radio-frequency energy that results in localized shrinkage of the stromal collagen directly related to the temperature and duration of exposure.…”
mentioning
confidence: 99%
“…Laser thermal keratoplasty studies [16][17][18]33 comment primarly on induced cylinder and rarely report loss of R2 Snellen lines.…”
Section: Safetymentioning
confidence: 99%
“…1-11 However, many patients are not good candidates for a hyperopic laser procedure and might opt for a thermokeratoplasty treatment. [16][17][18][19][20][21][22][23][24][25][26][27][28] The considerations are either anatomical, such as small corneal diameter, excessively steep or flat cornea, 8 deep eye orbit, dry-eye syndrome, or epithelial basement membrane dystrophy, or psychological, such as fear of a corneal cut or the idea of corneal tissue removal.Conductive keratoplasty (CK), a less-invasive procedure for the treatment of hyperopia and astigmatism, [19][20][21][22][23][24][25][26] does not involve flap creation and therefore flap-related complications, is nonlaser, produces a larger functional optical zone than LASIK, 24 significantly improves near vision, 25 and operates outside the central clear zone of the cornea.With CK, high-frequency (radio frequency 350 kHz), low-energy current is delivered within the stroma of the peripheral cornea with a keratoplasty tip inserted in the cornea. 26 The technique uses electrical properties of the…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of surgeons performing LTK agree on the low predictability of the technique. [3][4][5][6][7] However, a recent LTK study by Rocha et al 34 reported high predictability; 92% of the eyes were within G0.50 D of plano, and 100% within G1.00 D 2 years postoperatively.…”
Section: Subjective Evaluationmentioning
confidence: 99%